Vitamin D Status in Relation to the Clinical Outcome of Hospitalized COVID-19 Patients - Hafez, Wael; Saleh, Husam; Arya, Arun; Alzouhbi, Mouhamad; Fdl Alla, Osman; Lal, Kumar; Kishk, Samy; Ali, Sara; Raghu, Srinivasa; Elgaili, Walaa; Abdul Hadi, Wissam (Frontiers in Medicine, 2022)
Coronavirus Disease (COVID-19) is a newly emerged infectious disease that first appeared as a series of pneumonia cases in China. Vitamin D is a steroid hormone involved in the regulation of different immune responses. The study aimed to investigate the correlation between Vitamin D and clinical outcomes of COVID-19. This study was a retrospective study of 126 COVID-19 patients treated in NMC Royal Hospital in UAE. The mean age of the study population was 42.8 ±11.5 years. 83.3% patients were males, 50.8% were with sufficient (> 20 ng/mL), 41.3% were with insufficient (12-20 ng/mL), and 7.9% were with deficient (<12 ng/mL) Vitamin D. There was a statistically significant correlation between Vitamin D deficiency and mortality due to COVID-19 (p=0.036). There was a statistically significant correlation between Vitamin D and ICU admission (p= 0.030), but not with the need for mechanical ventilation (p=0.073). The results showed increased severity and mortality by 9% and 13%, respectively, for each one-year increase in age. This effect was maintained after adjustment for age and gender (Model-1) and age, gender, and co-morbidities (Model-2). Vitamin D (<12 ng/mL) showed a significant increase in mortality by 7.86 folds before adjustments (p=0.011) and by 11.87 folds in Model-1 (p=0.037); However, it lost its significance in Model-2. Vitamin D (< 20 ng/mL) showed no association with mortality before or after adjustment. Neither Vitamin D (<12 ng/mL) nor (< 20 ng/mL) were risk factors for severity before or after adjustment. Radiological findings were not significantly different among patients with different Vitamin D levels. Spite of observed shorter time till viral clearance and time from CRS to clinical recovery among patients with sufficient vitamin D levels, the findings were not statistically insignificant. In conclusion, we demonstrated a statistically significant correlation between Vitamin D and poor outcomes of COVID-19. Larger studies are recommended to determine the role of Vitamin D supplementation and the appropriate replacement protocol for patients at high risk.